Coffee and caffeine intake and depression in postpartum women: A cross-sectional study from the National Health and Nutrition Examination Survey 2007–2018 - Wang, Yinuo; Wang, Zhuangfu; Gui, Peijun; Zhang, Bo; Xie, Ying (Frontiers in Psychology, 2023)
This cross-sectional study examines the association between coffee and caffeine consumption and depressive symptoms in postpartum women. In total, 821 postpartum women who met the study’s inclusion criteria were interviewed. Data were extracted from the 2007–2018 National Health and Nutrition Examination Survey. Coffee consumption and 11 confounding variables were considered and analyzed as baseline data. Weighted logistic regression models were constructed by adjusting the variables, and the odds ratios of total coffee, caffeinated coffee, and decaffeinated coffee were assessed for their impact on depression status. In addition, subgroup analyses were conducted according to race, breastfeeding status, and postpartum period. The results show that generic coffee and caffeinated coffee intake have a potentially protective effect in postpartum women. Drinking more than three cups of caffeinated coffee may lower the risk of postpartum depression, particularly in the 1–2 year postpartum period and in non-breastfeeding women. The association between decaffeinated coffee consumption and postpartum depression remains unclear.